2016
DOI: 10.2205/2016es000572
|View full text |Cite
|
Sign up to set email alerts
|

Geohazard research, modeling, and assessment for disaster risk reduction

Abstract: Scientific understanding of lithosphere dynamics, earthquake occurrence, volcanic eruption, lava flow and other geohazards events as well as geophysical hazard assessments are greatly advanced for the last several decades. Meanwhile despite these major advancements, yet we are not seeing significant disaster risk reduction and a concomitant decline in disaster impacts and losses. There are at least two major issues that should be improved before significant reduction in disaster losses: enhancing geohazards re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Some of them are well known due to their great destructive power. These include earthquakes, volcanoes, landslides, and associated tsunamis (Ismail-Zadeh, 2016). Others generally do not cause direct damage to societies but can affect engineering structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are well known due to their great destructive power. These include earthquakes, volcanoes, landslides, and associated tsunamis (Ismail-Zadeh, 2016). Others generally do not cause direct damage to societies but can affect engineering structures.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic observations are included in geodynamic monitoring at foreign UGS [Scala et al, 2022], in Russia there are proposals to supplement traditional geodynamic monitoring for UGS with observations of seismicity [Nikonov, 2003], but so far this issue is under discussion and no evidence of technogenic seismicity during the operation of UGS in Russia has been cited. It is suggested that for a more complete account of geological hazards, it is necessary to take into account registered, historical and simulated earthquakes [Ismail-Zadeh, 2016]. Based on the analysis of the situation on Russian UGSs, the authors of this article believe that the manifestation of technogenic seismicity during their operation becomes a new reality that must be taken into account to ensure industrial and environmental safety.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are well known due to their great destructive power. These include earthquakes, volcanoes, landslides, and associated tsunamis [5]. Others generally do not cause direct damage to societies but can affect engineered structures.…”
Section: Introductionmentioning
confidence: 99%